EVIDENCE‑BASED POLICY AND PRACTICE: TANTANGAN DAN PENGEMBANGAN - Subhan, Haris (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Evidence-Based Policy and Pratice (EBPP) is something complex related to planning, implementation, and evaluation. Although the government and organization are seen as not having the capacity to implement it, the underlying problems can be identified. This article proposes a dimension of capability that might underlie practical improvements in EBPP. This framework addresses a spectrum of implementation problems at the organizational and individual levels that are vital for an evidence-based approach in the context of policy and practice.